Acute Concussion vs Post-Concussion Syndrome (PCS): How Can We Prevent Progression?. (4th January 2022) - Mahmood, Sheharzad; Przyslupski, Ann-Marie; Defreitas, Terry Lynn; Mrazik, Martin; Lebrun, Connie
Abstract : Objective: To contrast the presentation and recovery of acute concussion and post-concussion syndrome (PCS) in order to identify factors for PCS prevention. Background: Concussions are classified as acute (<90 days to resolution) or post-concussion syndrome (PCS, = 90 days to resolution). PCS poses a great burden to the individual and to public health. Further investigation is warranted for understanding the progression of acute concussion to PCS and potential mitigating strategies. Design/Methods: Retrospective chart review of concussion patients seen by Sports Medicine and Exercise Physicians over a five-year period. Outcome measures included demographics, wait-times, injury mechanisms, Sport Concussion Assessment Tool (SCAT) scores, management plans, and recovery timelines. Results: Four hundred ninety-six patients (289 male/207 female, 19.7 ± 9.4 years) presented with 561 concussions in 1, 471 visits. Acute concussions accounted for 88% of injuries and 12% were PCS. Females (RR = 1.4) and adults = 25 years (RR = 3.6) were more likely to be diagnosed with PCS. In both, injuries occurred most commonly in hockey, football, and soccer. Family physicians were the most frequent referral provider (58% acute, 76% PCS). Median injury-appointment time was 11.0 days (acute) compared to 182.0 days (PCS). Initial total SCAT symptom score was significantly greater ( p < 0.001 ) in PCS (56.0 ± 33.0) compared to acute concussion (39.8 ± 31.9). Therapies (i.e., referral, medication, intervention) were prescribed in 44% of acute injury visits compared to 73% of PCS visits. Recovery timelines for return to work, school, and sport were significantly longer in PCS patients than in those with acute concussions ( p < 0.05 ). Conclusions: Our findings of the incidence/presentation of PCS agree with previous literature. Athletes who are female and/or = 25 years may be at greater risk for PCS progression, requiring close monitoring and further injury prevention efforts. Considering the number of referrals from family physicians, further concussion education may better optimize initial management and shorten delays in seeking necessary sports medicine consultation.